God’s Rule: Government and Islam by Patricia Crone (New York: Columbia University Press, 2004. 462 pages.) (American Journal of Islam and Society, 2006)
Originally intended as a short textbook codifying the existing knowledge ofIslamic political thought, Patricia Crone’s God’s Rule developed into a fullerand more comprehensive examination of the first six centuries of governmentand Islam. Crone, perhaps better known for her more controversialworks, such as Hagarism (Cambridge: 1977), God’s Caliph (Cambridge:1986), and Meccan Trade and the Rise of Islam (Oxford: 1987), is nostranger to Islamic political theory, having written Slaves on Horses: The Evolution of the Islamic Polity (Cambridge: 1980). In her present book, thereader will find an accessible, readable, and scholarly contribution that islargely devoid of controversy while retaining a healthy skepticism of thesources, as one would expect from an historian.Primarily written for the non-specialist, the intention is to render thecontextual theory, practice, and development of political thought during theearly centuries of Islam (c. 622-1258) intelligible to the general reader.Divided into four sections, Crone seeks to cover the broader trends andthemes in the transition from the Prophet’s polity to that of the Buyids andthe Seljuqs. Along the way, she guides the reader through the complex webof Islamic history, starting, in part 1, with the basic Muslim conceptualunderstanding of government and state up to the first civil war, sect formation,and the Umayyad period. Here, the central importance was the leader,as successor to the Prophet, who weds truth and power and thereby rightlyguides the Muslim community by providing legal legitimacy and a moralexample. The question of legitimacy came to the fore during the first civilwar, which resulted in the formation of various sects and the rise of theUmayyad dynasty ...